Why do some research articles receive more online attention and higher altmetrics? Reasons for online success according to the authors - Kim Holmberg; Julia Vainio (Springer Netherlands, 2022)
Recent altmetrics research has started to investigate the meaning of altmetrics and whether altmetrics could reveal something about the attention or impact connected to research. This research continues this line of investigations and studies reasons for why some research has received significant online attention in one or both of two social media services; Twitter or Mendeley. This research investigated Finnish researchers’ opinions about the reasons for why their research had received significant online attention and if the attention received could reflect scientific or societal impact of their research. Furthermore it was studied whether the authors of the papers with significant online attention actively followed how their papers were shared or discussed online and if the authors thought that the online attention increased either the scientific or societal impact of their work. Based on the findings it can be stated that the level of online attention received is a sum of many factors and that there are also specific differences between the platforms where the attention has been received. For the articles that had received significant attention on Mendeley the reasons for that attention were more often seen as due to an academic audience, while the situation was reverse on Twitter, with the majority of reasons for the attention being linked to a wider audience. Similar trend could be seen when asked about whether the online attention could reflect scientific or societal impact, although a clear consensus about whether online attention could reflect any type of impact at all could not be reached.